Frank E. Vanderhoof papers - Vanderhoof, Frank E., 1888-
Correspondence, statements, transcripts of Congressional hearings and testimony, clippings, and other papers chiefly relating to Vanderhoof's plan for peace following World War II. Correspondents include William Agar, Gordon W. Allport, Joseph H. Ball, Andrew J. Biemiller, Christopher T. Boland, Harlan J. Bushfield, Lucy Jennings Dickinson, Emily Taft Douglas, Helen Gahagan Douglas, Alfred P. Haake, Clyde Roark Hoey, Arthur Norman Holcombe, Eric A. Johnston, Frank Kingdon, Alfred M. Landon, Augustine Lonergan, Louis Ludlow, Wayne L. Morse, Pope Pius XII, Ruth R. Reed, James H. Ryan, H. Alexander Smith, Harrison E. Spangler, Arthur Sweetser, Glen Hearst Taylor, Otto D. Tolischus, John W. Vandercook, Jerry Voorhis, and Y. C. James Yen.
In part, positive and negative photocopies and typewritten transcripts.
Economist and internationalist.
Collection material in English.
Forms part of: Miscellaneous Manuscripts collection.
Keywords: Agar, William -- Correspondence; Allport, Gordon W. -- 1897-1967 -- Correspondence; Ball, Joseph H. -- 1905-1993 -- Correspondence; Biemiller, Andrew J. -- 1906-1982 -- Correspondence; Boland, Christopher T. -- 1915- -- Correspondence; Bushfield, Harlan J. -- 1882-1948 -- Correspondence; Dickinson, Lucy Jennings, -- 1882-1971 -- Correspondence; Douglas, Emily Taft, -- 1899-1994 -- Correspondence; Douglas, Helen Gahagan, -- 1900-1980 -- Correspondence; Haake, Alfred P. -- 1885-1961 -- Correspondence; Hoey, Clyde Roark, -- 1877-1954 -- Correspondence; Holcombe, Arthur N. -- 1884-1977 -- Correspondence; Johnston, Eric A. -- 1895-1963 -- Correspondence; Kingdon, Frank, -- 1894-1972 -- Correspondence; Landon, Alfred M. -- 1887-1987 -- Correspondence; Lonergan, Augustine, -- 1874-1947 -- Correspondence; Ludlow, Louis, -- 1873-1950 -- Correspondence; Morse, Wayne L. -- 1900-1974 -- Correspondence; Pius -- XII, -- Pope, -- 1876-1958 -- Correspondence; Reed, Ruth R. -- Correspondence; Ryan, James H. -- 1886-1947 -- Correspondence; Smith, H. Alexander -- 1880-1966 -- Correspondence; Spangler, Harrison E. -- 1879-1965 -- Correspondence; Sweetser, Arthur, -- 1888-1968 -- Correspondence; Taylor, Glen Hearst, -- 1904- -- Correspondence; Tolischus, Otto D. -- 1890- -- Correspondence; Vandercook, John W. -- 1902-1963 -- Correspondence; Voorhis, Jerry, -- 1901-1984 -- Correspondence; Yen, Y. C. James, -- 1893-1990 -- Correspondence; World War, 1939-1945 -- Peace; Economists; Internationalists